1999
DOI: 10.1046/j.1365-201x.1999.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of testosterone and oestradiol on region specificity of skeletal muscle‐ATP, creatine phosphokinase and myokinase in male and female Wistar rats

Abstract: Arterial pulse pressure (PP) increases with exertional stress and ageing, and can modify vessel diameter in smaller vessels. To test if PP must exceed a certain range to influence vessel diameter, and determine if such effects are endothelium-dependent or intrinsic to vascular viscoelasticity, eight fresh excised porcine carotid artery segments were perfused with modified Krebs-Henseleit by a servo-controlled system generating physiological arterial pressure waveforms. In a separate group of vessels (n = 10), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…The functional significance of gonadal derived sex steroid hormones has been extensively studied; however, it is only recently that the importance of local extragonadal derived sex steroid hormones in cell physiology and pathophysiology is beginning to be appreciated in tissues such as the nervous, adipose, and adrenal gland (38). In the skeletal muscle cell, interest and evidence supporting a role for local sex steroid hormones, namely testosterone and estrogen, has recently been widely reported (16,17,35,41,43,49). However, the exact source of these hormones is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional significance of gonadal derived sex steroid hormones has been extensively studied; however, it is only recently that the importance of local extragonadal derived sex steroid hormones in cell physiology and pathophysiology is beginning to be appreciated in tissues such as the nervous, adipose, and adrenal gland (38). In the skeletal muscle cell, interest and evidence supporting a role for local sex steroid hormones, namely testosterone and estrogen, has recently been widely reported (16,17,35,41,43,49). However, the exact source of these hormones is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone and estradiol affect growth, strength, metabolism, and antioxidants in the skeletal muscle (16,17,35,39,40). Administration of testosterone has been reported to induce an increase in muscle strength with accretion of protein synthesis in the muscle (46).…”
mentioning
confidence: 98%
“…Previous studies have shown gender differences in gastrocnemius fiber type morphometry, size and number, which could be due to the different sex-related hormonal milieu [14,15]. Furthermore, measuring ATP contents, creatine phosphokinase and myokinase enzyme activities, Ramamani et al [38] found differences in skeletal muscle metabolism between genders, which were also linked to the hormonal status. The present results show that the activity of skeletal muscle mitochondrial oxidativephosphorylative complexes are higher in females, which could be indicative of a more efficient muscle energy metabolism compared to males, although further studies including mitochondrial function would be necessary to clarify this point.…”
Section: Effect Of Gender and Caloric Restriction In Muscle Mitochondmentioning
confidence: 95%
“…First, creatine has an important role in regulating brain energy metabolism (Allen, 2012; Andres et al, 2008), and evidence indicates that creatine supplementation benefits individuals with significantly elevated energy demands or metabolic dysregulation (Ipsiroglu et al, 2001; McMorris et al, 2006; Watanabe et al, 2002). Gonadectomy is known to cause significant impairments in energy metabolism in brain and muscle tissue, which may account for the positive outcomes of creatine’s effects on plasticity-related mRNA expression in castrated and ovariectomized rats (Irwin et al, 2008; Kemper et al, 2013; Li et al, 2011; Oner et al, 2008; Ramamani et al, 1999; Shi and Xu, 2008). Castration advances mitochondrial degeneration and muscle atrophy (Oner et al, 2008), reduces ATP content and creatine kinase activity (Ramamani et al, 1999), and activates apoptotic pathways that cause mitochondrial dysfunction in male rats (Li et al, 2011), whereas androgen replacement improves or reverses damage to mitochondrial structure and function in castrates (Koenig et al, 1980a b; 1982; Ramamani et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Gonadectomy is known to cause significant impairments in energy metabolism in brain and muscle tissue, which may account for the positive outcomes of creatine’s effects on plasticity-related mRNA expression in castrated and ovariectomized rats (Irwin et al, 2008; Kemper et al, 2013; Li et al, 2011; Oner et al, 2008; Ramamani et al, 1999; Shi and Xu, 2008). Castration advances mitochondrial degeneration and muscle atrophy (Oner et al, 2008), reduces ATP content and creatine kinase activity (Ramamani et al, 1999), and activates apoptotic pathways that cause mitochondrial dysfunction in male rats (Li et al, 2011), whereas androgen replacement improves or reverses damage to mitochondrial structure and function in castrates (Koenig et al, 1980a b; 1982; Ramamani et al, 1999). Similarly in females, ovarian hormone withdrawal precipitates impairments in energy metabolism by interfering with enzymes (including creatine kinase) and transcription factors that regulate mitochondrial biogenesis and efficiency in the brains of rodents, including hippocampal neurons, whereas replacement with EB, P, or EB+P restores mitochondrial function and metabolic rates (Irwin et al, 2008; Kemper et al, 2013; Ramamani et al, 1999; Shi and Xu, 2008).…”
Section: Discussionmentioning
confidence: 99%